Variability on Seed Yield and Related Agronomic Traits in Mesoamerican Common Bean (Phaseolus vulgaris L.) Genotypes under Contrasting Environments at South Eastern Ethiopia - Yimam, Kedir; Mekonnen, Fikru; Amsalu, Berhanu (International Journal of Bio-resource and Stress Management, 2023)
The experiment was conducted during July-November, 2022 at Melkassa and Kulumsa Agricultural Research Center main station under rain fed condition to assess the extent of genetic variability and to identify potential candidate genotypes. A total of 64 small seeded common bean genotypes were evaluated for 18 quantitative traits using 8*8 triple lattice design. The analysis of variance showed that there was highly significant (p<0.01) difference among genotypes for all studied traits at both individual locations. The genotypes variation for seed yield was ranged from 1685.09 kg ha-1 to 4499 kg ha-1 at Melkassa and from 1369.76 kg ha-1 to 4848.38 kg ha-1 at Kulumsa. High PCV and GCV were recorded for total number of seeds per plant, number of fertile pods and total number of pods plant-1 in both locations. Moderate to high value of GCV and broad sense heritability coupled with high GAM were obtained for seed per plant, dry pod yield per plant, fertile pods per plant, seed weight per plant, hundred seed weight and seed yield per hectare in both locations; indicating the importance of those traits in yield improvement of small seeded common bean. G-39, G-27, G-58, G-35, G-29, G-18, G-8, G-61, G-37 and G-33 showed yield advantage from 49% to 88.9% at Melkassa and G-33, G-8, G-4, G-12, G-58, G-11, G-45, G-13, G-36 and G-30 from 16% to 36% at kulumsa over the best standard check G-64. The existed variations implied the possiblity for further improvement of seed yield and atributing traits through utlizing selected potential genotypes and targeted hybridization schemes in breeding programs.